2001
DOI: 10.1128/jcm.39.6.2173-2177.2001
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Detection of the Human Herpesvirus 6-Specific Genomes in the Livers of Children with Various Liver Diseases

Abstract: This study was performed to investigate the frequency of human herpesvirus 6 (HHV-6) infection of the liver in children with a variety of liver diseases and to evaluate the role of HHV-6 infection in pediatric patients with prolonged non-B non-C hepatitis. Detection of the HHV-6 genomes in liver, in peripheral blood mononuclear cells (PBMC), and in plasma was performed by PCR or by in situ hybridization. Liver biopsy materials from 48 patients, in whom HHV-6 infection was serologically confirmed, were availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 22 publications
4
22
0
1
Order By: Relevance
“…However, HHV-6 DNA has also been amplified from liver tissue [8,9,23,24] and HHV-6 antigen was detected in hepatocytes [9]. Of note, replication of HHV-6 in a hepatoma cell line suggested that HHV-6 may indeed replicate in hepatocytes also in vivo [25].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, HHV-6 DNA has also been amplified from liver tissue [8,9,23,24] and HHV-6 antigen was detected in hepatocytes [9]. Of note, replication of HHV-6 in a hepatoma cell line suggested that HHV-6 may indeed replicate in hepatocytes also in vivo [25].…”
Section: Discussionmentioning
confidence: 96%
“…Recently, several studies suggested a role for HHV-6 in the pathogenesis of hepatitis, in particular graft hepatitis [5][6][7]. HHV-6 was detected both in lymphocytes and hepatocytes [8,9] but the clinical relevance of HHV-6 in graft hepatitis, for example an association of HHV-6 infection and graft survival, has not been proven so far [10].…”
Section: Introductionmentioning
confidence: 99%
“…These individuals included transplant recipients with their donors, and patients suspected of having an acute-or convalescent-phase herpesvirus infection. DNA was extracted from the samples and HHV-6 DNA was detected by PCR as previously described TanakaTaya et al, 1996;Fujisaki et al, 1998;Miyoshi et al, 2001;Ozaki et al, 2001;Sugimoto et al, 2002]. At least two additional PBMC samples were obtained examined from individuals whose PCR was positive for HHV-6.…”
Section: Samplesmentioning
confidence: 99%
“…The host tissue range of HHV-6 in vivo is even broader. It includes brain tissue (60,110,248), liver tissue (155,186,319), tonsillar tissue (347), salivary glands (130), and endothelium (55). Bone marrow progenitors were found to harbor latent HHV-6, which may be transmitted longitudinally to differentiated blood cells of different lineages (251).…”
Section: Cell Tropismmentioning
confidence: 99%